A Novel Layered WO3 Derived from An Ion Etching Engineering for Ultrafast Proton Storage in Frozen Electrolyte. (5th January 2023) - Wang, Di; Xu, Tiezhu; Zhang, Miaoran; Ren, Zhenghong; Tong, Hao; Shen, Laifa
Abstract: Aqueous proton batteries/pseudocapacitors are promising candidates for next‐generation electrochemical energy storage. However, their development is impeded by the lack of suitable electrode materials that facilitate rapid transport and storage of protons. Herein, an open‐layered hydrous tungsten oxide (WO3 ·nH2 O) with larger layer spacing from Aurivillius Bi2 WO6 via ion etching is proposed. Particularly, the WO3 ·nH2 O electrode possesses a unique multi‐level nanostructure and presents superior rate performance (254 F g −1 at 1000 mV s −1, surpassing most carbon‐based electrode materials known). In situ X‐ray Diffraction combined with crystallography study demonstrate that the open layered structure with negligible structural strain enables fast and reversible (de)intercalation of protons during electrochemical reaction. Furthermore, a full proton pseudocapacitor (Prussian blue analogues//WO3 ·nH2 O) operating in a wide temperature range from −40 to 25 °C is fabricated. This device can deliver 70% of the room‐temperature capacitance and stably cycle with negligible capacitance fading over 5000 cycles even in the solid‐phase electrolyte at −20 °C. This study provides a valuable strategy to design electrode materials with layered structures for the development of high‐performance aqueous proton batteries/pseudocapacitors at low temperatures. Abstract : A novel hydrous tungsten oxide with layered crystal structures is designed by the ion etching engineering. The open space between layers and varied protons binding sites facilitate rapid transport and reversible intercalation/deintercalation of protons. A full proton pseudocapacitor using this hydrous tungsten oxide as anode is fabricated, exhibiting great performance in the temperature from −40 to 25 °C.